CROSS-CULTURAL TEACHING OF A FOREIGN LANGUAGE - A NEW PARADIGM IN EDUCATION - Sobir Amirovich Khamzaev, Sobir Amirovich Khamzaev (Журнал иностранных языков и лингвистики, 2021)
This article examines the cultural approach in teaching a foreign language as a component of the students’ cross-cultural competence. Teaching a foreign language involves its use as a tool for the presentation of national culture in a foreign language and the knowledge of foreign culture, the formation of students’ cross-cultural communicative competence, the education of a multicultural personality acting as a mediator of cultures or a person immersed in the context of universal culture and various languages.